Formitamidine thiosulfate second-order nonlinear optical crystal and preparation and application thereof

By combining the strategy of heterocoordinated tetrahedron [SO3S]2- group and organic cationic group [CH(NH2)2]+, a second-order nonlinear optical crystal of formidine thiosulfate with a non-center symmetric crystal structure was synthesized, solving the problem of existing materials having strong second harmonic generation response and large birefringence, achieving the effect of crystallization in a non-center symmetric space group, and demonstrating a strong frequency doubling effect and wide optical band gap.

CN119753847AActive Publication Date: 2025-04-04TONGJI UNIV

Patent Information

Application Number
CN202411989315.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing ultraviolet sun blind second-order nonlinear optical materials are difficult to combine strong second harmonic generation response and large birefringence, and are difficult to crystallize in a non-center symmetric space group.

Method used

Using the strategy of combining heterocoordinated tetrahedron [SO3S]2-group and organic cationic group [CH(NH2)2]+, a second-order nonlinear optical crystal of formidine thiosulfate with a non-center symmetric crystal structure was successfully synthesized through the synergistic effect of elemental substitution and π-conjugated molecular orbital.

Benefits of technology

The crystal material exhibits a large birefringence, strong frequency doubling effect and a wide optical band gap. It can output 532nm green light under 1064nm laser irradiation, and is suitable for applications such as laser frequency converters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753847A_ABST
    Figure CN119753847A_ABST
Patent Text Reader

Abstract

The invention relates to a formamidine thiosulfate second-order nonlinear optical crystal and preparation and application thereof, the chemical formula of the crystal material is [CH (NH2) 2] 2SO3S, the molecular weight is 203.27, the crystal material belongs to an orthorhombic crystal system, the space group is P212121, the unit cell parameter is # imgabs 0 # alpha = beta = gamma = 90 degrees, Z = 4, and the unit cell volume is # imgabs 1 #. Under 1064nm laser irradiation, the frequency doubling intensity of the powder is about two times that of monopotassium phosphate crystals, and phase matching can be realized. In addition, the crystal material has a wide light transmission wave band, the ultraviolet absorption cut-off edge is 253 nm, the optical band gap is 4.90 eV, and the crystal material is easy to grow. The wavelength range of the coherent light source can be expanded by using optical frequency conversion technologies such as second harmonic generation and optical parametric amplification. Therefore, the crystal material has important application value in the fields of laser frequency conversion, photoelectric information storage and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonlinear optical crystal materials and relates to a formamidine thiosulfate second-order nonlinear optical crystal and preparation and application thereof. Background Art

[0002] Nonlinear optical (NLO) materials are widely used in laser frequency doubling, electro-optic modulation, optical storage, optical limiting and optical switching, and are an important material basis for realizing modern information technology with optoelectronics as the core. Among them, ultraviolet solar blind (solar blind, 210~280nm) second-order nonlinear optical materials have important applications in secure communication networks, fire monitoring systems and food sterilization. 4 ] 3- and [SO 4 ] 2- Non-π conjugated groups such as [SO] have a wide energy gap and have attracted extensive attention. However, traditional phosphates / sulfates often have difficulty in having strong second harmonic generation (SHG) response and large birefringence. 4 ] 2- Group, polar tetrahedron [S 2 O 3 ] 2- There are significant improvements in polarizability anisotropy and first-order hyperpolarizability, while maintaining a wide energy gap. The introduction of organic planar π-conjugated units can synergistically improve the polarizability anisotropy of the compound. However, there is a large dipole interaction between organic nonlinear units, which makes it difficult to crystallize in a non-centrosymmetric space group (non-centrosymmetric structure is a prerequisite for the material to generate second harmonics). From the perspective of optical performance, ultraviolet second-order nonlinear optical crystal materials often find it difficult to have both a strong powder frequency doubling effect and a moderate birefringence. Therefore, the development of ultraviolet second-order nonlinear optical crystal materials with non-centrosymmetric crystal structures is a hot topic and difficulty in current research. Summary of the invention

[0003] The purpose of the present invention is to provide a second-order nonlinear optical crystal of formamidine thiosulfate and its preparation and application. 3 S] 2- The groups greatly enhance the nonlinear optical properties of thiosulfate formamidine. The organic cationic groups [CH(NH 2 ) 2 ] + With π conjugated molecular orbitals, the crystal material exhibits a large birefringence (0.13@546nm) and a strong frequency doubling effect (2×KH 2 PO 4 (KDP)@1064nm), and a wide optical bandgap (4.9eV).

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] In one aspect, the present invention provides a second-order nonlinear optical crystal of formamidine thiosulfate, the chemical formula of which is [CH(NH 2 ) 2 ] 2 SO 3 S, molecular weight is 203.27, belongs to the orthorhombic system, and its space group is P2 1 2 1 2 1 , the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is

[0006] Furthermore, the unit cell parameters of the optical crystal are α=β=γ=90°, Z=4. Further preferably, the unit cell parameters are α=β=γ=90°, Z=4. Most preferably, the unit cell parameters are α=β=γ=90°, Z=4.

[0007] The crystal structure of formamidine thiosulfate of the present invention is as follows Figure 1 As shown. Each [SO 3 S] 2- The tetrahedron is formed by 1 central S atom coordinated with 3 O atoms and 1 S atom, and the SO bond length is The bond length of S=S is [CH(NH 2 ) 2 ] + and [SO 3 S] 2- The tetrahedra are connected to each other through NH··O hydrogen bonds. 3 S] 2- The groups greatly enhance the nonlinear optical properties of thiosulfate formamidine. The organic cationic groups [CH(NH 2 ) 2 ] + The π-conjugated molecular orbital makes the crystal exhibit a large birefringence.

[0008] In the second aspect, the present invention provides a method for preparing thiosulfate formamidine second-order nonlinear optical crystals, which comprises mixing a N source, a S source and water, and continuously stirring until a clear and transparent solution is obtained, and then naturally evaporating the solvent to finally obtain colorless and transparent flaky crystals, which are the target product.

[0009] Furthermore, the added amounts of the S source and the N source satisfy the following: the molar ratio of the S element to the N element is (1-10):(2-20).

[0010] Further, the S source is at least one of sodium thiosulfate, potassium thiosulfate and ammonium thiosulfate. Preferably, the S source is sodium thiosulfate.

[0011] Further, the N source is at least one of formamidine hydrochloride and formamidine. Preferably, the N source is formamidine hydrochloride.

[0012] Furthermore, the temperature at which the solvent evaporates is 25 to 55°C.

[0013] Furthermore, the time for the solvent to evaporate is not less than one week.

[0014] In a third aspect, the present invention provides an application of a formamidine thiosulfate second-order nonlinear optical crystal in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.

[0015] Furthermore, when the formamidine thiosulfate second-order nonlinear optical crystal material is used in a laser frequency converter, it can output 532nm green light under 1064nm laser irradiation.

[0016] The present invention utilizes the strategy of element substitution to replace the heterocoordinate tetrahedron [SO 3 S] 2- As a functional unit, it is combined with a π-conjugated group [CH(NH 2 ) 2 ] + The reaction successfully synthesized [CH(NH 2 ) 2 ] 2 SO 3 S. Heterocoordinate tetrahedron [SO 3 S] 2- The groups greatly enhance the nonlinear optical properties of thiosulfate formamidine. The organic cationic groups [CH(NH 2 ) 2 ] + The π-conjugated molecular orbital makes the crystal material present a large birefringence (0.13@546nm), while formamidine thiosulfate shows a strong double frequency response (2×KDP) and a short ultraviolet absorption cutoff edge (253nm).

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) The present application provides a new second-order nonlinear optical crystal [CH(NH 2 ) 2 ]2 SO 3 S, the crystal material has a large frequency doubling effect, which is about twice the frequency doubling intensity of KDP crystal under 1064nm laser irradiation, and can achieve phase matching. In addition, the crystal material has a high transmittance in the 253-800nm ​​spectral range, and the ultraviolet absorption cutoff wavelength is 253nm. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.

[0019] (2) The present application provides the nonlinear optical crystal [CH(NH 2 ) 2 ] 2 SO 3 The preparation method of S is to grow colorless flakes of [CH(NH 2 ) 2 ] 2 SO 3 The method is simple in process, mild in conditions, and easy to grow single crystals with high optical quality and high purity, which is conducive to large-scale industrial production.

[0020] (3) The formamidine thiosulfate crystal material of the present invention can be applied to a laser frequency converter, and can be used to output a laser beam as a doubled frequency harmonic. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the crystal structure of formamidine thiosulfate;

[0022] Figure 2 is a comparison of X-ray diffraction patterns; (a) is an X-ray diffraction pattern obtained by analyzing and simulating the single crystal X-ray diffraction data of sample 1#; (b) is a pattern obtained by X-ray diffraction testing after sample 1# is ground into powder;

[0023] Figure 3 is the UV-Vis-NIR absorption spectrum of sample 1#;

[0024] Figure 4 is the infrared spectrum of sample 1#;

[0025] Figure 5 This is the thermogravimetric analysis spectrum of sample 1#;

[0026] Figure 6 It is the second harmonic signal diagram of sample 1# and KDP sample with size ranging from 200 to 280 μm;

[0027] Figure 7 This is the second harmonic phase matching diagram of sample 1# at a wavelength of 1.064μm. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0029] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0030] Embodiment 1:

[0031] Preparation of samples 1# to 8#

[0032] The S source, N source and water are mixed in a certain proportion to form a raw material, placed in a polytetrafluoroethylene liner, and stirred continuously until a clear and transparent solution is obtained. Then the solvent is slowly evaporated at room temperature, and finally a colorless and transparent flake [CH(NH 2 ) 2 ] 2 SO 3 S crystal.

[0033] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 1.

[0034] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0035]

[0036] Crystal structure analysis of samples 1# to 8#

[0037] Single crystal X-ray diffraction and powder X-ray diffraction techniques were used to perform structural analysis and phase analysis on samples 1# to 8#, respectively.

[0038] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0039] Single crystal X-ray diffraction results show that samples 1# to 8# have the same chemical formula and crystal structure, with the chemical formula being [CH(NH 2 ) 2 ] 2SO 3 S, molecular weight is 203.27, belongs to the orthorhombic system, and its space group is P2 1 2 1 2 1 , the unit cell parameters are α=β=γ=90°, Z=4.

[0040] Take sample 1# as a typical example, its crystal structure data is α=β=γ=90°, Z=4. [CH(NH 2 ) 2 ] 2 SO 3 The crystal structure of S Figure 1 shown.

[0041] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu Kα, a wavelength of The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.

[0042] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 8#, the peak positions of each sample are basically the same, but the peak intensities are slightly different.

[0043] Take sample 1# as a typical example. Figure 2 As shown, according to the crystal structure analyzed by single crystal X-ray diffraction, the peak positions of the fitted X-ray diffraction pattern are consistent with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, which indicates that the obtained sample has a high purity.

[0044] UV-Vis absorption spectrum test

[0045] The diffuse reflectance absorption spectrum test of sample 1# was conducted on a Cary 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 3 As shown, the compound has no absorption in the range of 253 to 800 nm and an optical band gap of 4.9 eV.

[0046] Infrared spectrum test

[0047] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown, 704cm -1 、1062cm-1 The characteristic absorption peak at 3 S] 2- The presence of groups, 1644 cm -1 、1713cm -1 、3035cm -1 and 3173cm -1 The characteristic absorption peak at 2 ) 2 ] - The presence of groups.

[0048] Thermogravimetric testing

[0049] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 5 As shown, the thermal decomposition temperature of this compound is 170°C.

[0050] Frequency doubling test experiment and results

[0051] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a spectrometer is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the control sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, with the particle size ranges of 26-50, 50-105, 105-150, 150-200, and 200-280μm, respectively. Observe the trend of the frequency doubling signal intensity changing with the particle size to determine whether phase matching can be achieved. Under the same test conditions, compare the second harmonic intensity generated by the sample and the KDP sample to obtain the relative size of the sample frequency doubling effect.

[0052] The test results show that the compound thiosulfate formamidine crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is twice that of the control sample KDP crystal (such as Figure 6 ), phase matching can be achieved (such as Figure 7 ).

[0053] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A formamidine thiosulfate second-order nonlinear optical crystal, characterized in that: Its chemical formula is [CH(NH2)2]2SO3S, its molecular weight is 203.27, it belongs to the orthorhombic crystal system, its space group is P212121, and its unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is 2. The formamidine thiosulfate second-order nonlinear optical crystal according to claim 1, characterized in that: The unit cell parameters of the optical crystal are: α=β=γ=90°, Z=4.

3. The method for preparing a formamidine thiosulfate second-order nonlinear optical crystal according to claim 1 or 2, characterized in that: The N source, S source and water are mixed and stirred continuously until a clear and transparent solution is obtained, and then the solvent is naturally evaporated to finally obtain colorless and transparent flaky crystals, which are the target product.

4. The method for preparing the formamidine thiosulfate second-order nonlinear optical crystal according to claim 3, characterized in that: The added amounts of the S source and the N source satisfy the following requirement: the molar ratio of the S element to the N element is (1-10):(2-20).

5. The method for preparing the formamidine thiosulfate second-order nonlinear optical crystal according to claim 3, characterized in that: The S source is at least one of sodium thiosulfate, potassium thiosulfate and ammonium thiosulfate.

6. The method for preparing the formamidine thiosulfate second-order nonlinear optical crystal according to claim 3, characterized in that: The nitrogen source is at least one of formamidine hydrochloride and formamidine.

7. The method for preparing the formamidine thiosulfate second-order nonlinear optical crystal according to claim 3, characterized in that: The temperature at which the solvent evaporates is 25 to 55°C.

8. The method for preparing the formamidine thiosulfate second-order nonlinear optical crystal according to claim 3, characterized in that: The solvent should evaporate for at least one week.

9. Application of the formamidine thiosulfate second-order nonlinear optical crystal as claimed in claim 1 or 2 in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.

10. The use of a formamidine thiosulfate second-order nonlinear optical crystal according to claim 9, characterized in that: When the second-order nonlinear optical crystal material of formamidine thiosulfate is used in a laser frequency converter, it can output 532nm green light under 1064nm laser irradiation.

Citation Information

Patent Citations

  • Heterobimetal sulfate nonlinear optical crystal material as well as preparation method and application thereof

    CN113235164A

  • Guanidine lutetium formate second-order nonlinear optical crystal material and preparation and application thereof

    CN119061483A

  • Ammonium zinc thiocyanate second-order nonlinear optical crystal material and preparation and application thereof

    CN119065174A

  • Organosilicon compounds containing s-alkylthiosulfate groups, processes for their preparation and use of the same

    US5210249A

Cited By

  • Lithium 2-hydroxyethanesulfonate second-order nonlinear optical crystal and preparation and application thereof

    CN121496572A

  • A lithium 2-hydroxyethanesulfonate second-order nonlinear optical crystal, its preparation and application

    CN121496572B

  • Halogen esilate second-order nonlinear optical crystal and preparation and application thereof

    CN121496573A